An estimation to the Andean pattern construction & community territory management - Arroyo Hurtado, Roberto (2019)
The political and cultural dimension of globalization brought the weakening and restructuring of the Nation-State in the centralized countries. In societies where the coloniality of power and knowledge are still dominants, a set of very complex processes entails the return of the territory as a communal construction as a Demiurge of the change time. There emerge some sustainable processes aimed at the appropriation, revaluation, recreation and resignification of territories, in addition to traditional and ancestral principles and practices open to transcultural processes that transport germs of the new one to a world surrounded by climate change and threatened by the deepening of the inequalities in all social areas. The objective of this text, based on an investigation promoted by the Ricardo Palma University (URP), is to approach this process from the central macrozone of the country.